Comparative Analysis of International Experience and Outcome Indicators in the Application of the Liberal Market Model in Electricity - Hajiyev, Timur (ADA University, 2023)
In recent decades, there has been a significant change in the global energy sector, as more and more nations are choosing to liberalize their power markets. This master thesis conducts a thorough comparative examination of global practices in adopting the liberal market model in the electrical sector, with a particular emphasis on the situation in Azerbaijan. This research examines the reasons, difficulties, and results linked to the process of liberalization, with the goal of obtaining valuable information that may guide policy choices and strategic development for the energy sector in Azerbaijan. The research is motivated by the acknowledgement that energy market liberalization is a widespread global phenomenon, influenced by the need for economic effectiveness, heightened competition, and the incorporation of renewable energy sources. Azerbaijan, blessed with substantial energy resources, has initiated a process to deregulate its electricity market in order to improve operational effectiveness, attract capital investments, and guarantee a viable energy future. The aims of this thesis are to examine global instances of electricity market liberalization, discern recurring trends, and evaluate the particular difficulties and results witnessed in the Azerbaijani setting
Keywords: Energy market liberalization – Global perspective – Comparative analysis; Electricity market deregulation – Azerbaijan; Energy policy – Azerbaijan – Market reform; Renewable energy – Market integration – Azerbaijan; Economic efficiency – Energy markets – Global trends; Azerbaijan – Energy sector – Policy and regulation; Azerbaijan – Energy market – Deregulation challenges; Energy security – Azerbaijan – Market liberalization effects; IT and Engineering